(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
The article presents data on the accumulation, excess of the maximum permissible concentration of cadmium in irrigated sierozem-meadow, desert-sandy, as well as gray-brownmeadow soils of the Nishan district of the Kashkadarya region